This is what happy looks like - Smith, Jennifer E., 1980- (Poppy, 2013)
"Perfect strangers Graham Larkin and Ellie O'Neill meet online when Graham accidentally sends Ellie an e-mail about his pet pig, Wilbur. The two 17-year-olds strike up an e-mail relationship from opposite sides of the country and don't even know each other's first names. What's more, Ellie doesn't know Graham is a famous actor, and Graham doesn't know about the big secret in Ellie's family tree. When the relationship goes from online to in-person, they find out whether their relationship can be the real thing"--